Pengaruh Harga dan Promosi Terhadap Keputusan Pembelian Mobil Produk Wuling (Studi Pada Konsumen Mobil Wuling di Kota Semarang) - Rizal Putra Amanda; Sendhang Nurseto (Universitas Diponegoro, 2019)
In the modern era like today in carrying out its activities, humans are increasingly dependent on machine assistance, especially in the field of transportation. One of them is a car. Wuling Motors is a Chinese vehicle brand run by Liuzhou Wuling Automobile Industry Co., Ltd. Based on data from the Indonesian Automotive Industries Association (Gaikindo) in 2018, Wuling sales in every month always increase and at the beginning of 2018 it can enter into the 10 best-selling brands in 2018, but the problems that occur in the sales figures in the last 5 months have not yet reached company sales target. This study aims to find out how the influence given by price and promotion to the purchase decision of Wuling car in Semarang City. The type of research used is explanatory research where the data collection technique used is by using questionnaire tool, the sample used amounted to 100 people by using purposive sampling technique. Respondents selected are consumers who make purchasing decisions Wuling car in Semarang City. The methodology used to analyze primary data in this research is validity test, reliability test, correlation coefficient, coefficient of determination, simple linear regression, multiple linear regression, and significance test (t and F test) with SPSS 16.0. The results showed that price significantly influence the purchase decision of 31.5% while the balance is influenced by many factors beside price. Promotion has a significant effect on purchasing decision of 40,4% while the balance is explained by many factors beside promotion. Meanwhile, simultaneously price and promotion have a significant effect on purchasing decision equal to 49,3% while the balancing influenced by many factors beside price and promotion. It means better the price and promotion, the higher the purchase decision of Wuling car. In addition, the promotion has the greatest influence with regression coefficient value of 0.587. Based on the results of the study, the researchers have suggestion for Wuling Motors providing quality products that are better at increasing promotions and providing prices that are in accordance with the value of the products offered.